The South American genus Lagideus Konow (Hymenoptera: Pergidae: Syzygoniinae), a Supplement - Smith, David R. (Zootaxa, 2012)
Six new species of the Neotropical pergid genus Lagideus are described and illustrated: Lagideus boyaca, L. magdalena, L. schmidti, and L. flavus from Colombia and L. tapanti, and L. isidro from Costa Rica. Lagideus romius Smith is newly recorded from Colombia and the female lancet is illustrated. Females are described for the first time for Lagideus longicus Smith from Costa Rica and L. albitarsis Malaise from southeastern Brazil, Uruguay, and Argentina.